2021
DOI: 10.3390/jcm10112333
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the GHB Withdrawal Syndrome

Abstract: The gamma-hydroxybutyric acid (GHB) withdrawal syndrome can have a fulminant course, complicated by severe complications such as delirium or seizures. Detoxification by tapering with pharmaceutical GHB is a safe way to manage GHB withdrawal. However, a detailed description of the course of the GHB withdrawal syndrome is currently lacking. This study aimed to (1) describe the course of GHB withdrawal symptoms over time, (2) assess the association between vital signs and withdrawal symptoms, and (3) explore sex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…However, amongst convenience samples of some demographic groups, such as lesbian, gay, and bisexual people, rates 20-54 times greater have been recorded (Hammoud et al 2018;Mooney-Somers et al 2020). A global systematic review identified growing evidence for GHB-related adverse effects amongst people who use GHB regularly (Dijkstra et al 2021). Harms associated with the use of GHB include overdose and use disorder (Schep et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, amongst convenience samples of some demographic groups, such as lesbian, gay, and bisexual people, rates 20-54 times greater have been recorded (Hammoud et al 2018;Mooney-Somers et al 2020). A global systematic review identified growing evidence for GHB-related adverse effects amongst people who use GHB regularly (Dijkstra et al 2021). Harms associated with the use of GHB include overdose and use disorder (Schep et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The onset of withdrawal can be rapid-commencing within an hour of discontinuation and peaking at 24 h-and can last up to 3 weeks (Schep et al 2012). While the clinical characteristics of a withdrawal syndrome have not been well defined in the literature, case studies and reviews describe similarities between withdrawal symptoms of GHB and other CNS depressants such as alcohol or benzodiazepines (Wojtowicz et al 2008;Wolf et al 2021). The Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5), characterises a withdrawal syndrome associated with sedative, hypnotic, or anxiolytic drugs by two or more symptoms including autonomic hyperactivity (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As memory problems were also frequently observed by the nursing staff in patients with GUD who applied for detoxification, we included patients referred to these clinics. Detoxification for patients with GUD often takes place in an inpatient setting, due to the potential fulminant course of GHB withdrawal [26]. During their stay patients’ withdrawal is closely monitored while they are gradually tapered off with pharmaceutical GHB according to the Dutch GHB guideline [6, 7, 27].…”
Section: Introductionmentioning
confidence: 99%